First Evidence of Microplastics in Human Urine, a Preliminary Study of Intake in the Human Body - Concetta Pironti; Valentina Notarstefano; Maria Ricciardi; Oriana Motta; Elisabetta Giorgini; Luigi Montano (Toxics, 2022)
The ubiquitous presence of microplastics (MPs) and their health effects is a recent scientific topic. However, the investigation of MPs in human/biological matrices has several limitations due to analytical methods and sample treatment protocols. In this study, the presence of MPs in the urine samples of six volunteers from different cities in the south of Italy (three men and three women) was investigated by Raman microspectroscopy. The analysis pinpointed four pigmented microplastic fragments (4–15 μm size), with irregular shapes, which were characterized in terms of morphology and chemical composition. Polyethylene vinyl acetate (PVA), polyvinyl chloride (PVC), polypropylene (PP), and polyethylene (PE) MPs were found in four samples (PVA and PVC in one female sample and PP and PE in three male samples). This preliminary study suggests that MPs could pass through the gastrointestinal tract and are eliminated through biological processes.